Assessing and changing attitudes and behaviours toward intimate partner violence in southern Africa as a primary prevention method for HIV infection - Riddle, Alison (University of Ottawa (Canada), 2009)
Reducing intimate partner violence levels in southern Africa is a necessary component of an effective HIV primary prevention strategy. A prerequisite to behaviour change is a shift in attitudes. This study sought to identify effective ways of assessing and changing attitudes and behaviours towards IPV to prevent HIV infection in a developing country context. Combining a systematic review of current evidence with advanced statistical analyses of data from a southern Africa regional household survey (n = 20,639), Soul City Regional Evaluation Phase 1, findings indicate that: a gold standard to measure IPV attitudes and behaviours is needed; interventions targeting structural change and based in the community are more effective; the effectiveness of mass media interventions may not be robust; the interaction of different prevention interventions may mediate overall effectiveness. Exploratory factor analysis, multiple imputation, and regression techniques were applied to complex, multileveled, and correlated data with missingness.
Keywords: Health Sciences, Nursing.; Health Sciences, Public Health.